Boğazköy-Ḫattuša, Türkei: Restaurierungen - Schachner, Andreas (e-Forschungsberichte des DAI, 2023)
Restoration work has been conducted parallel to archaeological research at Boğazköy-Hattusha continuously since the 1960s when P. Neve first established a method to conserve the excavated buildings on the one hand and to make them visible for the visitors on the other. During the last years (2011– 2014) work concentrated on the reconstruction and restoration of the socalled postern wall, the oldest fortification of the Hittite city, the placement of copies of the two sphinxes on top the artificial rampart of Yerkapı and the conservation of the large worked socle stones of the Great Temple in the Lower Town, the most important Hittite religious building.